The Smell of the Dead in London, c. 1700–1850 - Christ, Martin (Renaissance and Reformation / Renaissance et Réforme, 2025)
While some scholars in eighteenth-century England identified a link between the smell of the dead and the spread of diseases, it was not until the nineteenth century that the dead were no longer buried in London’s inner-urban churchyards. This article draws attention to the multiplicity of voices when it came to the links between bad smells and disease and argues that whether there was a connection between the two was by no means a matter of scholarly consensus. While some hygiene reformers emphasized the possibility of the spread of diseases through the air, others opposed this view, and while theories about miasma retained some influence, they were also challenged and debated. This article therefore challenges a linear narrative of the movement of dead bodies from inner-urban cemeteries to the outskirts of towns based on fears that the dead might spread harmful vapours. It argues instead that already in the eighteenth century, prominent medical professionals questioned the connection between a pollution of the air through the dead and a spread of diseases. Even in the nineteenth century, there was no straightforward deodorization effort, but it was rather the confluence of a range of different factors, only one of which involved concerns about hygiene, that led to the relocation of burial sites. Taking the example of the English metropolis of London, this article shows that considering the smell of the dead can enhance our understanding of the functioning and planning of towns as well as the spaces of the dead more generally.